ANALISIS HASIL BALAJAR MATEMATIKA SISWA PADA METERI MATRIKS MELALUI PEMBELAJARAN BERBASIS E-LEARNING - Abdul Wahab Abdullah; Dewi Rahmawaty Isa; Nur Fajriani Podungge (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2021)
This study aims to describe students' mathematics learning outcomes in matrix material through e-learning based learning. This research was conducted at SMK Negeri 2 Limboto with a descriptive method involving 21 students as the research sample selected by purposive sampling technique. Data collection was obtained from the results of mathematics learning tests involving several indicators, namely: (1) understanding, (2) application, (3) analysis, (4) synthesis, and (5) evaluation. The results showed that students' mathematics learning results through e-learning-based learning were in the poor category, which was indicated by the percentage of scores achieved by students of 69%.